The three-prong method: a novel assessment of residual stress in laser powder bed fusion. Issue 1 (2nd January 2018) - Sillars, S. A.; Sutcliffe, C. J.; Philo, A. M.; Brown, S. G. R.; Sienz, J.; Lavery, N. P.
ABSTRACT: Residual stress is a major problem for most metal-based laser powder bed fusion (L-PBF) components. Residual stress can be reduced by appropriate build planning and post-process heat treatments; however, it is not always avoidable and can lead to build failures due to distortion and cracking. Accurate measurement of residual stress levels can be difficult due to high equipment set-up costs and long processing times. This paper introduces a simple but novel method of measuring residual stresses via a three-pronged cantilever component, the three-prong method (TPM). The method allows for a quick and easy characterisation of residual stress for a wide range of machine parameters, build strategies and materials. Many different cantilever designs have been used to indicate residual stress within additive manufacturing techniques. All of which share the same shortcoming that they indicate stress in one direction. If the principal component of stress is not aligned with the beam geometry, it will underestimate peak stress values. A novel three-prong design is proposed which covers two dimensions by utilising three adjoined cantilever beams, a configuration which echoes that of hole-drilling where three measurements are used to calculate the stress field around a drilled hole. Each arm of the component resembles a curved bridge-like structure; one end of each bridge is cut away from the base plate leaving the centre intact. Deformation of the beams is then measured using a co-ordinate measurement machine. Stress profiles are then estimated using finite element analysis by meshing the deflected structure and forcing it back to its original shape. In this paper, the new TPM is used to compare the residual stress levels of components built in Ti–6Al–4V with different hatch patterns, powers and exposure times.